2020
DOI: 10.1007/s11845-020-02382-5
|View full text |Cite
|
Sign up to set email alerts
|

The correlation between Jun N-terminal kinase pathway-associated phosphatase and Th1 cell or Th17 cell in sepsis and their potential roles in clinical sepsis management

Abstract: Background We aimed to investigate the association between Jun N-terminal kinase (JNK) pathway-associated phosphatase (JKAP) and T helper type 1 (Th1) cell or Th17 cell, and their clinical values in sepsis patients. Methods Totally 125 sepsis patients and 100 healthy subjects as controls were included. Peripheral blood was extracted from each sepsis patient and each control, then serum and peripheral blood mononuclear cell (PBMC) were separated. JKAP and inflammatory cytokines were detected in serum by ELISA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
22
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 25 publications
3
22
0
Order By: Relevance
“…A very recent study suggests that Th1 and Th17 cell proportions are associated with increased septic mortality risk 16 . In this study, it was observed that Th1 and Th17 cell proportions were both elevated in septic deaths compared with survivors.…”
Section: Discussionsupporting
confidence: 48%
See 3 more Smart Citations
“…A very recent study suggests that Th1 and Th17 cell proportions are associated with increased septic mortality risk 16 . In this study, it was observed that Th1 and Th17 cell proportions were both elevated in septic deaths compared with survivors.…”
Section: Discussionsupporting
confidence: 48%
“…Although it has been addressed that Th1 and Th17 cells play vital roles in the progression of sepsis, 9‐14 the proportions of Th1 and Th17 cells in patients with sepsis remain largely unclear. One previous study suggested that RAR‐related orphan receptor‐γ protein and T‐bet are both reduced in elderly sepsis patients compared with elderly patients with infection alone, indicating decreased Th1 and Th17 cell proportions in elderly septic patients, 15 while another very recent study reported that in sepsis patients, Th1 and Th17 cell proportions are elevated compared with healthy subjects 16 . However, these studies are restricted by their small sample sizes, and Th1, Th17 cell proportions in sepsis patients should be further validated with larger sample sizes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In terms of regulation of CD4 + T cells, JKAP is reported to repress CD4 + T‐cell activation as well as its differentiation into Th1 and Th17 cells in systemic lupus erythematosus nephritis and inflammatory bowel disease 12,13 . Clinically, JKAP negatively correlates with Th17 cell secreted IL‐17 in inflammatory bowel disease patients, and negatively correlates with Th1 cells as well as Th17 cells in sepsis patients 12,23 . But to date, the relation between JKAP and CD4 + T cells in PD patients is not uncovered yet.…”
Section: Discussionmentioning
confidence: 99%